1995
DOI: 10.7164/antibiotics.48.793
|View full text |Cite
|
Sign up to set email alerts
|

Terpendoles, Novel ACAT Inhibitors Produced by Albophoma yamanashiensis. III. Production, Isolation and Structure Elucidation of New Components.

Abstract: Eight new components of terpendoles E to L were isolated and characterized from the culture broth of Albophomayamanashiensis using a different production medium. All the structures were elucidated by spectroscopic analyses including various NMRexperiments, indicating that all the terpendoles have the same indoloditerpene core as terpendoles A to D. Terpendoles J, K and L showed the moderate inhibition against acyl-CoA : cholesterol acyltransferase (ACAT)activity with IC50 values of 38.8, 38.0 and.32.4//m in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 23 publications
5
58
0
Order By: Relevance
“…Despite no direct evidence for the pathway leading to 11,12‐epoxides, terpendole B is proposed as the first 11,12‐epoxide based on the observation that it occurs in Albophoma yamanashiensis , along with other terpendoles, notably terpendoles E, F, and G [24,25], even though it was not identified in this study. The biosynthetic scheme proposed (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Despite no direct evidence for the pathway leading to 11,12‐epoxides, terpendole B is proposed as the first 11,12‐epoxide based on the observation that it occurs in Albophoma yamanashiensis , along with other terpendoles, notably terpendoles E, F, and G [24,25], even though it was not identified in this study. The biosynthetic scheme proposed (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…They have been somewhat arbitrarily classified into six structural groups, namely the penitrems, janthitrems, lolitrems, aflatrem, paxilline and the paspaline/paspalinine/paspalitrems (Steyn and Vleggaar 1985). To these groups can be added the more recently discovered terpendoles (Huang et al 1995;Tomoda et al 1995;Gatenby et al 1999), shearinines (Belofsky et al 1995), sulpinines (Laakso et al 1992), nodulisporic acid (Ondeyka et al 1997) and thiersinines (Li et al 2002). All these compounds have a cyclic diterpene skeleton derived from four isoprene units, and an indole moiety derived from tryptophan or a tryptophan precursor (Acklin et al 1977;de Jesus et al 1983;Laws and Mantle 1989), but very little is known about the pathways for their biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…By detailed analyses of its NMR data, we found that the NMR data of 2 are very similar to those of the closely related compound, terpendole L, a known indole diterpenoid reported from Albophoma yamanashiensis. [13] The only difference is that the position of an isopentenyl group at C-20 in terpendole L was migrated at C-22 in 2, as confirmed by HMBC and COSY experiments ( Figure 2). The relative configuration of 2 was established as the same as that of terpendole L by comparing their NMR data, as well as analyses of the NOESY correlations of H-5α with H-7/H-25, H-7 with H-6α/H-9, H-10 with H-11/H-35, and H-26 with H-6β/H-11/H-16 ( Figure 3).…”
Section: Resultsmentioning
confidence: 85%